Impact and vulnerability assessment on climate change of Jessore and Mymensingh districts in Bangladesh - Afrin, N; Habiba, U; Das, RR; Auyon, ST; Islam, MA (Progressive Agriculture, 2019)
A survey of Jessore and Mymensingh district, the study assesses the inclusive scenario of climate change and its impact over 30 years (From 1981 to 2016). The objective of the study is to assess the overall condition of Jessore and Mymensingh district over last three decades which is being influenced by changing climate pattern. The research area is comprised of ten sub-districts in the Jessore and Mymensingh district, two separate geographic regions in Bangladesh, where climate change literature has highlighted as prone to accelerated degradation. Four-hundred (400) respondents participated in the questionnaire survey, both quantitative and qualitative data were collected and analyzed using SPSS, the data were also used to calculate weighted indexes for rankings and to perform logistic correlation. Results showed that climate change, a critical global environmental challenge which showed rigorous impacts as “extreme temperature” in both Jessore district and Mymensingh district. In case of climate change vulnerability “water resources” was brutally vulnerable to climate change in both Jessore and Mymensingh district followed by another four resources. Moreover, the climate risks most frequently addressed in existing studies were associated with “risk of natural disaster” in Jessore district and “surface water quality” in case of Mymensingh district. Conversely “fish farming” was the most operational adaptation measures to climate change in Jessore district and in Mymensingh district “use of different crop varieties” was mostly percept by the respondents. In case of constraints related to adaptation measures “Lack of proper awareness” was the most terrible constraints to climate change adaptation faced by the respondents regarded as top in ranking order, followed by other adaptation constrains in Jessore district and “Limited knowledge about adaptation measures” in case of Mymensingh district. Also, questionnaire survey was done in ten (10) different GOs and NGOs in Jessore and Mymensingh district for the accurateness of the consequence of climate change in the study regions which also disclosed that increased temperature, erratic precipitation, increase ground water uses, increased flood frequency, drought frequency etc. were some major consequences of climate change in the two study districts. These results provide policy makers and development service providers with important insight, which can be used to better target interventions which build, promote or facilitate the adoption of adaptation mechanisms with potential to build resiliency to changing climate and resulting environmental impacts. Progressive Agriculture 29 (4): 320-335, 2018